Answer:
x = 13 − 2 = 11 ∘ F
Step-by-step explanation:
Let the original temperature be
I = x .
Final temperature
F = − 2 ∘
Change in temperature
C = I − F = x − ( − 2 ) = ( x + 2 ) ∘ F
But it’s given change in temperature
C = 13 ∘ F
Therefore,
C = 13 = ( x + 2 )
∴ x + 2 = 13 or x = 13 − 2 = 11 ∘ F
-------------------------------------------------------------------------------------------------
Step-by-step explanation:
Another way to approach this question, without algebra, is to approach it this way:
We know that at the end of the time period, it's − 2 ∘ F. At the beginning of the time period, it was
13 ∘ F warmer. And so we can say that the temperature at the beginning of the time period can be found by adding − 2 and 13 :
− 2 + 13 = 11 ∘ F